Formulation, characterization, in vitro and in vivo evaluations of self-nanoemulsifying drug delivery system of luteolin. Issue 1 (1st January 2020) - Ansari, Mohammad Javed; Alshetaili, Abdullah; Aldayel, Ibrahim Abdulaziz; Alablan, Faisal Mohammed; Alsulays, Bader; Alshahrani, Saad; Alalaiwe, Ahmad; Ansari, Mohd Nazam; Ur Rehman, Najeeb; Shakeel, Faiyaz
Abstract : The purpose of this study was to develop a self-nanoemulsifying drug delivery system (SNEDDS) for the improvement of solubility and bioavailability of luteolin in order to enhance its therapeutic benefits. Formulations were prepared by spontaneous emulsification method which involved low energy mixing of appropriate amounts ofcastor oil, kolliphor & polyethylene glycol 200. The developed formulae were optimized and characterized for self-nanoemulsifying capacity, thermodynamic stability, size behaviour and solubility. The globule size of the optimized formula F1–A1:1 was 112 ± 15 nm, with narrow PDI (0.31 ± 0.09) and good zeta potential (−16.2 ± 3.2 mV). The optimized formula exhibited approximately 83, 17 and 3-fold enhancement in the solubility in vitro release and ex vivo permeation respectively. The luteolin SNEDD exhibited better antioxidant activity (DPPH scavenging activity) than ascorbic acid. Per cent inhibition in rat paw oedema by the SNEDDS formulation was statistically significant when compared with luteolin suspension at equivalent dose ( P  < 0.05).